Association of Maternal Age with Mental Health in Pregnant Women in Agricultural Communities : A Cross-Sectional Study in Bogor, Indonesia - Ryadi, Yusuf; Sumulyo, Ganot; Sarkowi, Widya Khairunnisa; Hanif, Aisyah Amanda; Dewi, Mira (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Mental health issues such as depression and anxiety during pregnancy can significantly impact pregnancy outcomes. Agriculture is a high-stress industry that might increase the risks of depression and anxiety. Women in agricultural communities often experience a dual burden from physically demanding labor and reproductive responsibilities, with limited access to mental health services and social support—making them particularly vulnerable. Aims: This study aimed to identify factors contributing to depression and anxiety among pregnant women in an agricultural community in Bogor Regency. Methods: This cross-sectional study was conducted from August to October 2023 in Bogor Regency, West Java. A total of 69 pregnant women attending Cijeruk Primary Health Care were involved. Data were collected via interviews and medical records. Depression and anxiety levels were assessed using the Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS). Results: The majority of subjects (>60%) had no depression or anxiety. The prevalence of severe and very severe depression was 10.1%, and 5.8% for severe and very severe anxiety. Maternal age was negatively correlated with both depression (r = -0.317, p = 0.008) and anxiety scores (r = -0.332, p = 0.005). No significant associations were found between HDRS scores and other factors such as gestational age, education level, household income, physical activity, or farming family background. Conclusion: The correlation between maternal age and depression and anxiety scores highlights the importance of promoting mature age in premarital counseling. Further research is needed to explore broader determinants of maternal mental health in agricultural communities with larger, more diverse samples.